Comparative study of criminal liability of legal entities in Iran and the Council of Europe - Mohammad Moradi; Azade Sadeghi; Esmaeil Haditabar (پژوهشنامه حقوق تطبیقی, 2021)
Despite the new approach in the Penal Code, no definition of a legal entity is provided, and the legislative view in Article 143 of the Penal Code, in order to hold a legal entity liable, is subject to two conditions, namely or in the interests of the legal entity. Due to the difficulties in assigning responsibility, the scope of punishment of the legal entity is associated with many issues that need to be fundamentally reformed because the legal entity has gradually become very important and this is hidden in the activity and how it is formed. The commission of a crime by a legal person not only has a profound effect on society, but its effects are much more lasting and, in most cases, involve governments. The problem becomes more complicated when we encounter a person whose criminological findings are not possible to correct and restore society to these people because they lack understanding and will. In contrast, the Council of Europe is more favorable. The responsibility of legal entities is on the EU's political agenda. have been. The Council of Europe, by creating a method of identification, analysis of different levels of criminal responsibility, creating diversity in laws, diversity in attribution mechanisms, advanced organizational model, classification of crimes committed, typology of punishment, etc., appropriate and developed orientation Has.